Development and research trends of a polypropylene material in electrical engineering: A bibliometric mapping analysis and systematical review - Duan, Yubing; Zhao, Yonggui; Ma, Guoqing; Sun, Xiaobin; Zhang, Hao; Liu, Wenbo (Frontiers in Energy Research, 2023)
In order to explore the development and research trends of polypropylene (PP) in electrical engineering, the research literature is quantitatively analyzed using a bibliometric method with the VOSviewer and CiteSpace software. First, the research literature about PP material in electrical engineering applications is collected, from 1990 to 2022. Then, by analyzing the keyword co-occurrence, keyword co-occurrence timezone, author cooperation network, and national cooperation network, the research hotspots of the PP field and its time evolutionary path and development direction are introduced. It is found that the nano-modification, mechanical, and electrical properties are the most popular research hotspots in this field. Most research studies were completed by few specific researchers. A stable cooperative group has not been formed in this field yet, indicating the necessity of further integration. Most articles about PP were published in dielectric and material journals. It is suggested that more open access journals are required to popularize the existing research results among the public and to promote the development of PP. Although the most published country is China, the United States publishes the most cited papers on average.